2014
DOI: 10.1590/0101-7438.2014.034.02.0275
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Selection of Information Systems Projects Using Promethee v With C-Optimal Concept

Abstract: This paper presents a multicriteria decision model for selecting a portfolio of information system (IS) projects, which integrates strategic and organizational view within a multicriteria decision structure. The PROMETHEE V method, based on outranking relations is applied, considering the c-optimal concept in order to overcome some scaling problems found in the classical PROMETHEE V approach. Then, a procedure is proposed in order to make a final analysis of the c-optimal portfolios found as a result of using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, the PROMETHEE V method [75] employs the concepts of boundary portfolios which are maximal in the sense that they cannot accommodate more projects without violating resource constraints, and c-optimal portfolios that are deemed as optimal when considering only c projects. Furthermore, [1] applied some MCDA methods for selecting a portfolio of information system projects considering strategic, technical, and organizational criteria. Moreover, [80] developed a three-step process, in which Analytic Network Process was used to evaluate influence, power, and performance scores of suppliers in a green supply chain.…”
Section: A Review Of Selected Solution Methods For Portfolio Decisionmentioning
confidence: 99%
“…For example, the PROMETHEE V method [75] employs the concepts of boundary portfolios which are maximal in the sense that they cannot accommodate more projects without violating resource constraints, and c-optimal portfolios that are deemed as optimal when considering only c projects. Furthermore, [1] applied some MCDA methods for selecting a portfolio of information system projects considering strategic, technical, and organizational criteria. Moreover, [80] developed a three-step process, in which Analytic Network Process was used to evaluate influence, power, and performance scores of suppliers in a green supply chain.…”
Section: A Review Of Selected Solution Methods For Portfolio Decisionmentioning
confidence: 99%
“…Although no studies using MCDA with the same goal as this study by have been found, it was possible to identify other studies in the area of project management, such as: on project management selection and activities priorization (Zavadskas et al, 2008;Hadad et al, 2013;Dodangeh et al, 2014;Mota et al, 2009;Gurgel & Mota, 2013); team decision-making (Collier, 2013;Alencar & Almeida, 2010); portfolio management (Arasteh et al, 2014;Almeida et al, 2014;); and project management competencies analysis (Chipulu et al, 2013).…”
Section: The Fundamental Skills and Abilities Of The Project Managermentioning
confidence: 99%
“…Authors have proposed many approaches to the decision‐making process in the IT project portfolio management, such as the real options theory (Angelou & Economides, 2008), modern portfolio theory (Esfahani et al, 2016), neural networks (Costantino et al, 2015), heuristic methods (Chang et al, 2009), stochastic dominance models (Yeh et al, 2010), optimization models (Baizyldayeva et al, 2013), multicriteria model (Almeida et al, 2014; Ghapanchi et al, 2012; Pinho & Ebecken, 2009), hybrid multicriteria (Pinheiro et al, 2013), among others.…”
Section: Introductionmentioning
confidence: 99%